Efektivitas gel ekstrak jahe gajah (Zingiber officinale var rosc) terhadap kecepatan kesembuhan luka abrasi pada tikus putih (Rattus novergicus) jantan strain wistar - erwien isparnadi; Fatah Jati Pamungkas; Diah Hermayanti; yoyok Subagio (Universitas Syiah Kuala, 2022)
Abstract. Background: Abrasion wound is the release of the skin surface caused by friction with rough surface, ginger anti-inflammatory compound so that it can accelerate the healing of abrasion wounds. Objective: the effectiveness of healing abrasion wounds with gel application of ginger extract (Zingiber Officlinale Var Rosc) on white rats (Rattus norvegicus). Method: True experimental with post test only control group design. The study was conducted for 7 days with samples divided into 4 groups, P1 (NaCl 0.9%), P2 (Gel 0%), P3 (Ginger Gel 8%), P4 (Ginger Gel 12%). Application of extract gel was done on days 1, 3 and 5. Wound area observed on day 7. Data analyzed using the One Way ANOVA test. Results: The results showed abrasion wound area day 7 at P1 = 1.47 cm2, P2 = 0.58 cm2, P3 = 0.31 cm2, P4 = 0 cm2, healing speed P1 = 4.9% / day, P2 = 10.6% / day, P3 = 12.31% / day, P4 = 14.2% / day. One way ANOVA test results showed a significant effect (p 0.05). Conclusion: Elephant ginger extract extract (Zingiber officinale var rosc) can accelerate healing of abrasion wounds in white rats (Rattus norvegicus).